MODERN MORPHOLOGY OF HEMATOPOIETIC ORGANS (Modern education and development, 2025)
Hematopoietic organs are complex structures that provide vital body functions. They are involved in the formation, development and destruction of blood cells. In this article, the morphological features of hematopoietic organs will be considered.